2012
DOI: 10.1016/j.envres.2011.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Household chemical exposures and the risk of canine malignant lymphoma, a model for human non-Hodgkin’s lymphoma

Abstract: Background Epidemiologic studies of companion animals offer an important opportunity to identify risk factors for cancers in animals and humans. Canine malignant lymphoma (CML) has been established as a model for non-Hodgkin’s lymphoma (NHL). Previous studies have suggested that exposure to environmental chemicals may relate to development of CML. Methods We assessed the relation of exposure to flea and tick control products and lawn-care products and risk of CML in a case-control study of dogs presented to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 22 publications
0
45
0
4
Order By: Relevance
“…It should be acknowledged that for most forms of cancer the aetiology is likely to be multifactorial and although genetics are important environmental factors such as chemical exposure [227] and hormonal/metabolic factors have been shown to increase the risk of development of certain tumours. …”
Section: Discussionmentioning
confidence: 99%
“…It should be acknowledged that for most forms of cancer the aetiology is likely to be multifactorial and although genetics are important environmental factors such as chemical exposure [227] and hormonal/metabolic factors have been shown to increase the risk of development of certain tumours. …”
Section: Discussionmentioning
confidence: 99%
“…A recent study [209] found a statistically-significant association between the use of “self-applied insect growth regulators” (OR = 2.7; 95% CI = 1.1–6.8) and canine lymphoma, but specific constituents were not identified. Associations between herbicides were not statistically significant (OR = 1.3; 95% CI = 0.9–1.8).…”
Section: Toxicological Studiesmentioning
confidence: 99%
“…Lymphoma is common in dogs, and resembles non‐Hodgkin lymphoma in humans. Epidemiologic studies have found significant associations between canine lymphoma and exposure to industrial pollutants, solvents and herbicides, but the role of specific environmental carcinogens in the development of lymphoma in dogs is not clear . GSTT1 activities have been characterized in livers from research beagles, and 12% of these dogs had virtually no GSTT1 protein expression or activity .…”
Section: Introductionmentioning
confidence: 99%